The embodiment of bhakti - Pechilis, Karen (Oxford University Press, 1999)
This work aims to offer an interpretive history of bhakti, an influential religious perspective in Hinduism. The author argues that although Bhakti is mentioned in every contemporary sourcebook on Indian religions, it still lacks an agreed-upon definition.